The REM Observing Software - Mauro Stefanon; Stefano Covino; Dino Fugazza; Emilio Molinari; Francesco D'Alessio; Giuseppe Malaspina; Luciano Nicastro; Vincenzo Testa; Gino Tosti; Fabrizio Vitali (Advances in Astronomy)
The Rapid Eye Mount (REM) is a 60 cm robotic telescope located at La Silla, Chile. Its Observing Software (REMOS) is constituted by a set of distributed intercommunicating processes organized around a central manager. Together they grant the system safety, automatically schedule and perform observations with two simultaneous cameras of user-defined targets, and drive fast reaction to satellite alerts. Subsequent data reduction is left to pipelines managed by each camera.